Étude ethnobotanique, ethno-taxonomique et ethnoécologique de Anacyclus pyrethrum var. pyrethrum (L.) Link. (Asteraceae) dans la vallée d’Ait Mhamed (Région d’Azilal, Maroc) - Abderrahim Ouarghidi; Abdelaziz Abbad (Revue d'ethnoécologie)
The roots of medicinal plants are an important part of the traditional Moroccan pharmacopoeia. Several issues of sustainability of this use have been raised. Anacyclus pyrethrum var. pyrethrum is among the medicinal plants that are, according to some, to be overharvested in the wild in Morocco. The present work is a contribution to an ethnobotanical, ethnotaxonomic and ethnoecological study of the A. pyrethrum var. pyrethrum in the valley of Ait Mhamed, considered one of the last refuges of the species in the central High Atlas. Ethnobotanical surveys of 28 collectors and 2 wholesalers showed that the root of A. pyrethrum var. pyrethrum is used as a dry powder to treat rheumatism of the lower limbs and lumbar vertebrae and gastroenteritis, and also used fresh against toothache and in the intimate hygiene of women. The ethnoecological study has shown that there is consensus among two groups of collectors (young and old) with respect to the ecology of the plant. There is a vertical transmission of ecological knowledge between generations, with young collectors interested in the roots ecology and sustainability because of its economic importance. The ethnotaxonomic study has shown that the collectors are very good at distinguishing between the root of iguendez (A. pyrethrum var. pyrethrum, the “true pyrethrum”) and that of tiguendizt (A. pyrethrum var. depressus or “false pyrethrum”). Collectors use the colour of the flowers, the shape and size of the root and the smell to tell these two apart and clearly refer to them as different species. The detailed knowledge held by collectors suggests that the substitution of iguendez with tiguendizt is voluntary and that accidental confusion is likely rare. This study has also shown that the local population is aware of the rarefaction of the species in its natural range and has a very important know-how in terms of its mode of management and conservation in situ.